Analyzing the determinant of intention to use digital platform application: a moderated mediation model - Sri Astuti Pratminingsih; Nabila Ghina Utami (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2022)
The purpose of this study is to analyse and examine the factors that determine customer intention to use Halodoc, a digital platform application in health sector. This study employs e-service quality as one of the antecedents of customer intention, and attempts to examine the mediating role of perceived value. In addition, this study also uses perceived usefulness variable as moderating variable. The respondents of this study are 210 users of Halodoc application, who are chosen using purposive sampling technique. The data is analysed with conditional process analysis using SPSS Macro-PROCESS. This study contribute to several findings: (1) E-service quality has a positive influence on intention to use; (2) E-service quality has a positive influence on perceived value; (3) Perceived value has a positive influence on intention to use; (4) Perceived value mediates the influence of e-service quality on intention to use; (5) Perceived usefulness positively moderates the influence of perceived value on intention to use; and (6) Perceived usefulness positively moderates the indirect influence of e-service quality on intention to use through perceived value. This study also provides contribution to the literature and the business practice.